Materiality conflicts in dual suistanability-reporting regimes: indonesia’s transition from impact-based OJK rules to ISSB financial materiality - Chandra Erick Manaek Pandapotan Lumban Gaol; Tarsisius Murwadji; Beniadi Setiawan (Lentera Negeri, 2026)
The contemporary architecture of corporate sustainability reporting is undergoing an unprecedented epistemological rupture, transitioning from a localized, impact-oriented paradigm under the Indonesian Financial Services Authority (OJK) toward a globally standardized, financial-materiality framework promulgated by the International Sustainability Standards Board (ISSB). This paradigm shift, culminating in the ratification of PSPK 1 and PSPK 2 effective January 1, 2027, precipitates a profound jurisprudential paradox regarding regulatory compliance and corporate fiduciary duties within emerging markets. Traditional orthodox normative legal research has systematically failed to decode the sociological frictions inherent in this dual-regime landscape, often falsely dichotomizing the frameworks as either mutually exclusive or seamlessly harmonized (Abhayawansa, 2022; Adams & Mueller, 2022). Eradicating these archaic theoretical lacunae, this research operationalizes a cutting-edge methodological fusion, integrating Socio-Legal Analysis with Project-Based Legal Epistemology. By dissecting the "asymmetrical incomplete overlap" between POJK No. 51/POJK.03/2017's mandatory economic, social, and environmental disclosure floor and the ISSB’s investor-centric financial-materiality overlay, this study confronts the realities of symbolic compliance and governance-washing within the extractive and corporate sectors (Correa-Mejía et al., 2024; Dragomir et al., 2025). As a tangible project-based output, this manuscript engineers a highly prescriptive, four-step conflict-resolution protocol materialized through a concrete Academic Compliance Matrix. This matrix structurally reconciles dual-tagging mechanisms, value-chain boundary delimitations, and board-level accountability escalations, thereby establishing an indisputable, interoperable legal blueprint for transnational corporate governance and integrated compliance sustainability.